Exogenous lysozyme as an alternative to antibiotics improves growth performance and small intestinal morphology of broiler chickens - Hassan, Reda; Hassan , Reda Ali; Eid, Yahya Zakaria; Mohamed, Mohamed Abdel-Azeem (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
There have been successful attempts to replace antibiotics in broilers with dietary lysozyme (LYZ), but more study is required to ensure its efficacy. We investigated the effects of LYZ and the feed addition avelamycin (AVI) on broiler chickens' immunity, gastrointestinal health, and growth performance. Two hundred and seventy one-day-old broiler chicks (Ross 308) were randomly assigned to three groups, each consisting of six replicates and each consisting of fifteen birds. The standard diet without supplements was applied as control group (I), while chicks in the other groups were provided with 100 mg AVI per kg of diet (AVI, group II), and 90 mg LYZ per kg of diet (LYZ, group III) for five consecutive weeks. Result In comparison to the CON group, the AVI and LYZ groups showed significant (p<0.05) increases in body weight, feed conversion ratio, body weight growth, European production efficiency factor, protein efficiency ratio, and digestibility of crude protein; however, feed intake remained unchanged. IgG and IgM levels in the serum were greater in the lysozyme group than in the AVI and control groups. Comparing the serological haemagglutination inhibition titers of NDV vaccination to the control and AVI groups, the LYZ-treated group showed a substantial increase (p < 0.05). Dietary 90 mg lysozymes dramatically reduced the amount of E. coli and total coliforms in the cecum while increasing Lactobacillus. Comparing the LYZ group to the AVI and control groups, the VH and VH/CD were significantly greater. In conclusion intestinal integrity, fecal bacterial counts, immunological response, and growth performance were all improved by exogenous dietary lysozyme supplementation at a level of 90 mg/kg broiler diet, and these results were on par with avilamycin. Thus, dietary lysozyme could be a safe substitute for avilamycin in the diet of broiler chickens.